A Biomechanical Comparison of Fiberglass Casts and 3-Dimensional–Printed, Open-Latticed, Ventilated Casts. (November 2020) - Hoogervorst, Paul; Knox, Riley; Tanaka, Kara; Working, Zachary M.; El Naga, Ashraf N.; Herfat, Safa; Lee, Nicolas
Background: The aim of this study was to quantify the stabilizing properties of a 3-dimensional (3D)-printed short-arm cast and compare those properties with traditional fiberglass casts in a cadaveric subacute distal radius fracture model.Methods: A cadaveric subacute fracture model was created in 8 pairs of forearms. The specimens were equally allocated to a fiberglass cast or 3D-printed cast group. All specimens were subjected to 3 biomechanical testing modalities simulating daily life use: flexion and extension of digits, pronation and supination of the hand, and 3-point bending. Between each loading modality, radiological evaluation of the specimens was performed to evaluate possible interval displacement. Interfragmentary motion was quantified using a 3D motion-tracking system.Results: Radiographic assessment did not reveal statistically significant differences in radiographic parameters between the 2 groups before and after biomechanical testing. A statistically significant difference in interfragmentary motion was calculated with the 3-point bending test, with a mean difference of 0.44 (±0.48) mm of motion.Conclusions: A statistically significant difference in interfragmentary motion between the 2 casting groups was only identified in 3-point bending. However, the clinical relevance of this motion remains unclear as the absolute motion is less than 1 mm. The results of this study show noninferiority of the 3D-printed casts compared with the traditional fiberglass casts in immobilizing a subacute distal radius fracture model. These results support the execution of a prospective randomized clinical trial comparing both casting techniques.